Overview historical and current of american trypanossomiasis in the Amazon: biological and epidemiological aspects - Manuela Kavata Ranucci; Dionatas Ulises de Oliveira Meneguetti (Universidade de Santa Cruz do Sul, 2012)
KEYWORKS Chagas diseases, Triatominae, Trypanosoma cruzi, Amazon